Effect of the Australian "Alcopops Tax" on Alcohol-Related Emergency Department Presentations for Injury in Two States - Lensvelt, Eveline; Liang, Wenbin; Gilmore, William; Gordon, Elise; Hobday, Michelle; Chikritzhs, Tanya (2016)
OBJECTIVE: The purpose of this study was to examine the impact of a specific tax increase on ready-to-drink beverages (the "alcopops" tax) on male injuries presenting to emergency departments during times likely to be highly alcohol related in two Australian states. METHOD: Poisson regression was used to compare annual risk of Western Australian and Victorian male emergency department injuries occurring during high alcohol-related times before and after the implementation of the alcopops tax. A range of age groups was examined. Surrogate methodology was applied to identify numbers of emergency department injuries that occurred during high and low alcohol-related times. RESULTS: Risk of injury during high alcohol-related times (incident rate ratio [IRR]) was lower among Western Australian 12- to 15-year-olds beginning from the year of the tax increase and continued throughout. Lower IRRs were also apparent for 15- to 19-year-olds, although some delay was implicated. There was no change for 12- to 15-year-old Victorians, but immediate declines were evident for 15- to 19-year-olds. To a lesser extent, delayed effects were also indicated for 20- to 29-year-olds in both states. There was no evidence of a change in injury risk during high alcohol-related times among the oldest age group (35-39 years). CONCLUSIONS: Previous research on beverage-specific taxes has suggested that they may increase alcohol-related harms among the target group. This study found no evidence of increased injury during high alcohol-related times associated with the alcopops tax in two states. Evidence of reduced harm was apparent, however, and strongest for Western Australian males aged 19 years and younger. These outcomes are consistent with documented national reductions in alcopops sales.